Management of distal tarsometatarsal fracfure in a Hill Mynah (Gracula religiosa) by using external coaptation technique - Abu, Jalila; Abdul Rahman, Nor Alimah; Ideris, Aini (Veterinary Association Malaysia, 2009)
An adult Hill Mynah (Gracula religiosa) was presented with non weight-bearing lameness on the left leg. A distal transverse fracture of the left tarsometatarsus was diagnosed by using radiography techniques. A combination of external coaptation using tape splint and ball bandage was applied. It was found that this combination technique resulted in a clinical union of the fractured site at three weeks post-treatment. This technique also provided perching and movement stability in the cage. The success of this combination technique offers another alternative for external coaptation in avian species.